Narrating evil to understand the tragedy in Colombia: the band Masacre and violence - Arboleda Álzate, Juan Camilo; Cuartas Restrepo, Juan Manuel (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
In this essay we will analyze the lyrics of the colombian band Masacre, which features armed violence as its main theme, as well as the tragedy that arises around it. The band resorts to real-life facts, thus mirrorring the principle of truth in the craft of news. It does not result, however, in a deviation from the use of symbols and other narrative forms enabled by music and its several and diverse components, thus weaving bridges between imagination and comprehension.